2013
DOI: 10.1021/es4018877
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Perfluoroalkyl Acid Precursors in AFFF-Impacted Groundwater and Soil

Abstract: Several classes of polyfluorinated chemicals that are potential precursors to the perfluorinated carboxylates and sulfonates are present in aqueous film-forming foams (AFFF). To assess the persistence of these AFFF-derived precursors, groundwater, soil, and aquifer solids were obtained in 2011 from an unlined firefighter training area at a U.S. Air Force Base where AFFF was regularly used between 1970 and 1990. To measure the total concentration of perfluorinated carboxylate and sulfonate precursors in archive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
596
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 659 publications
(629 citation statements)
references
References 32 publications
26
596
3
4
Order By: Relevance
“…In the study conducted in Norway, greater concentrations of RPFASs were found in waterproofing agents, which can be regarded as the same category as sprays for fabrics and textiles in this study, with the exception of aqueous firefighting foams (Houtz et al, 2013). In the study conducted in Germany, greater concentrations of FTOHs (up to 396 lg mL À1 ) were found in the category ''lubricants'' (LU 1 and LU2) (Fiedler et al, 2010).…”
Section: Comparison Of Current and Previous Study Resultssupporting
confidence: 51%
“…In the study conducted in Norway, greater concentrations of RPFASs were found in waterproofing agents, which can be regarded as the same category as sprays for fabrics and textiles in this study, with the exception of aqueous firefighting foams (Houtz et al, 2013). In the study conducted in Germany, greater concentrations of FTOHs (up to 396 lg mL À1 ) were found in the category ''lubricants'' (LU 1 and LU2) (Fiedler et al, 2010).…”
Section: Comparison Of Current and Previous Study Resultssupporting
confidence: 51%
“…Therefore, PFOS and its salts have been voluntarily phased-out by its major manufacturers and have been added to list of the Stock Convention on Persistent Organic Pollutants (Annex B, UNEP) [8]. Other polyfluorinated substances, such as 6:2 chlorinated polyfluorinated ether sulfonate (6:2 Cl-PFAES) and fluorotelomer sulfonates (FTSs) were also found in aqueous systems due to alternative usages [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorinated surfactants based on fluorotelomer thiol ( (Falk, 1984), e.g., F(CF 2 ) n CH 2 CH 2 SCH 2 CH(OH) CH 2 N + H(CH 3 )CH 2 CO 2 À ) and sulfonyl chemistry ( (Bertocchio and Foulletier, 1971) e.g., F(CF 2 ) n CH 2 CH 2 SO 2 NHCH 2 CH 2 N + (CH 3 ) 2 CH 2 CH 2 CO 2 À ) have also been used in AFFF. As a result of AFFF containing these fluorinated surfactants being used at fire training facilities to control and extinguish major Class B (i.e., flammable, combustible liquids and gases) fires, environmental degradation products such as PFSAs and fluorotelomer sulfonic acids (FTSAs) have been found in ground water and soil (Backe et al, 2013;Houtz et al, 2013). The perfluoroalkane sulfonyl surfactants degrade to the corresponding PFSA, e.g., PFOS, PFHxS, and PFBS (Moody and Field, 2000;Moody et al, 2003;Rhoads et al, 2008).…”
Section: Introductionmentioning
confidence: 99%